CLINICAL APPROACH OF DENTISTS TOWARDS REPAIR OF FRACTURED REMOVABLE COMPLETE DENTURES - Syeda Ridaa Fatima; Nida Zehra Bano; Muhammad Kaleem (Pakistan Oral & Dental Journal, 2022)
The objective of this study was fourfold; 1) To find out the approach of dentists working in the prosthodontics department towards a fractured complete denture, 2)To identify which kind of denture base fracture do dentists mostly encounter in their clinical practice, 3) To find the choice of material preferred by dentists for the repair of complete dentures and 4)To find out whether dentists use any polishing technique after the repair of a fractured denture. A cross-sectional study was conducted in four teaching dental hospitals; Armed Forces Institute Of Dentistry(AFID), Islamic International Dental Hospital, Rawal Dental Hospital, And Watim Dental Hospital in the twin cities of Pakistan from 1st to 20th of August 2021. A questionnaire comprising of seven questions was used and all the clinicians working in the prosthodontic department were targeted. The response rate was 80 percent. The collected data were analyzed and interpreted using IBM SPSS version 25. The frequency of categorical variables was calculated. Fischer exact test was used to evaluate the association between variables. The results indicate that a greater percentage of dentists prefer repair of fractured complete dentures instead of refabrication. Separation of a single tooth from the denture base is identified as the most common type of fracture. Heat cure acrylic was the preferred material for the repair of denture bases. The polishing technique was employed by a majority of dentists after the repair of denture bases. This study provided a unique result in contrast to other studies that reported midline as the most common type of denture fracture.
Keywords: Denture; Complete, Denture bases; Prosthodontics; Acrylic resins; Geriatric patients